Fish stocks of Urophycis Brasiliensis revealed by otolith fingerprint and shape in the southwestern Atlantic Ocean - Biolé, Fernanda Gabriela (2019)
Brazilian codling Urophycis brasiliensis is one of the main commercial coastal fish species from the Southwestern Atlantic Ocean. Regardless of its economic relevance, its stock structure remains largely unknown. In this study, we used the otolith shape and the core/outer edge multi-elemental fingerprints (Li:Ca, Mg:Ca, Mn:Ca, Fe:Ca, Zn:Ca, Rb:Ca, Sr:Ca, and Ba:Ca ratios) to evaluate the spatial segregation of young (nursery areas) and adult (stocks) stages of fish from the coast of northern Argentina, Uruguay, and southern Brazil. Otolith edge chemistry showed that several elemental ratios were significantly different between catching areas. Permutational multivariate analysis of variance (PERMANOVA) (p < 0.05) and quadratic discriminant analysis (QDA), with jackknifed classification of 80.0 and 68.2% for otolith core and edge, respectively, were effective in discriminating between sampling sites considering young and adult life stages. PERMANOVA analysis of otolith shape revealed multivariate significant differences between Argentina and Brazil (p ¼ 0.0001) individuals, whereas no differences were found between fish from Uruguay and Argentina (p > 0.05). QDA classification rates were relatively low for Uruguay (48.0%) and values of 66.7 and 70.0% were found for Brazil and Argentina, respectively. Our results not only show the presence of at least two fish stocks (Argentina and Brazil), with a third potential stock in Uruguay, but also suggest a strong spatial segregation during ontogeny.